2001
DOI: 10.1002/dvdy.1146
|View full text |Cite
|
Sign up to set email alerts
|

LI‐cadherin gene expression during mouse intestinal development

Abstract: LI-cadherin (Liver-Intestine cadherin) is a member of a subclass (7-D cadherins) within the cadherin superfamily. Although its cellular function as a cell-cell adhesion molecule has been demonstrated in cell culture studies, its physiological function still needs to be explored in the intact organism. After isolating the cDNA for mouse LI-cadherin, we generated specific antibodies against the overexpressed protein and studied its expression pattern in adult mouse tissues and mouse embryos. The mouse LI-cadheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 88 publications
(69 reference statements)
1
41
0
1
Order By: Relevance
“…[99][100][101][102] The main function of CDH17 is to mediate cell-cell adhesion and to act as an intestinal peptide transporter. [99][100][101][102] CDH17 is expressed in normal glandular epithelium of the GI tract and normal pancreatic ducts. 102 A few reports 101,102 found CDH17 was a highly sensitive marker for GI ADCs and neuroendocrine neoplasms.…”
Section: Review Of Selected Antibodiesmentioning
confidence: 99%
“…[99][100][101][102] The main function of CDH17 is to mediate cell-cell adhesion and to act as an intestinal peptide transporter. [99][100][101][102] CDH17 is expressed in normal glandular epithelium of the GI tract and normal pancreatic ducts. 102 A few reports 101,102 found CDH17 was a highly sensitive marker for GI ADCs and neuroendocrine neoplasms.…”
Section: Review Of Selected Antibodiesmentioning
confidence: 99%
“…[22][23][24][25] The main function of CDH17 is to mediate cellcell adhesion and to act as an intestinal peptide transporter. [22][23][24][25] CDH17 is expressed in normal glandular epithelium of the GI tract and normal pancreatic ducts. 25 A limited number of reports have demonstrated that CDH17 is a highly sensitive marker for GI adenocarcinomas and neuroendocrine neoplasms.…”
mentioning
confidence: 99%
“…So far, the expression pattern of zebrafish Ksp-cadherin has not been analyzed. In mice, temporal LI-cadherin expression was also observed during embryogenesis in the epithelia of the urogenital sinus at day 13.5 post coitus [40]. This temporally overlapping expression pattern of Ksp-and LI-cadherin at certain developmental stages might be a relict of their common phylogentic origin.…”
Section: Discussionmentioning
confidence: 80%
“…The tissue-specific expression of today's Ksp-and LI-cadherin in highly resorptive epithelial cells of the kidney and the intestine, respectively [40,43], might have been responsible for their survival during evolution. Interestingly, the recently identified zebra fish LI-cadherin ortholog [59] shows an expression pattern that resembles both mouse Ksp-and LI-cadherin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation